Economics of bull production through embryo transfer in cattle and buffalo - Misra, A K; Pant, HC (The Indian Journal of Animal Sciences, 2011)
The profitabiligy of ET technique has examined in cattle and buffalo when used for the production of AI sires of outstanding genetic merit using elite females as donors. The analysis indicated that in competent hands ET technique can be used efficiently for bull production and use of such bulls for AI can lead to more efficient production of milk with very little extra cost. This in turn can improve herd profitability by tremendous increase in annual rate of genetic gain. By producing the breeding bulls through ET technology, the increased cost ofeach [t'ozen semen dose by about 13 (cattle) or47 (buffalo) paisa is negligible compared to the current cost of about Rs 10 for each frozen semen dose and about Rs 50 for the delivery ofthe frozen semen doses.